Cancer Stem Cells - Anurogo, Dito (PT. Kalbe Farma Tbk., 2021)
This mini-review will discuss Cancer Stem Cells (CSCs) on their definition, history, characteristics, models, origin, tumorigenesis, targeting Cancer Stem Cells with nanomaterials, niche interactions, CSCs therapeutics, vaccination, the role of autophagy in CSCs, artificial intelligence, and clinical trials targeting CSCs.Â Mini review ini membahas sel punca kanker (Cancer Stem Cells), meliputi: definisi, sejarah, karakteristik, model, asal-mula, tumorigenesis, menarget CSCs dengan nanomaterial, interaksi niche, terapeutik berbasis CSCs, vaksinasi, peran autofagi pada CSCs, kecerdasan buatan, dan uji klinik menarget CSCs.